Strategi Bank Syariah Indonesia Dalam Mengatasi Ancaman Cyber - Baiq Leonyta Hayanu; Sulhan Hadi; Iwan Tanjung (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
The aim of this research is to analyze the Strategy of Indonesian Sharia Banks in Overcoming Cyber ​​Threats. The research method used in this research is descriptive qualitative with data collection methods of observation, interviews and documentation. Implementation of the cyber threat prevention process in maintaining the operational system at Bank Syariah Indonesia Pejanggik I Mataram Branch Office is the ability of all bank parties, including leaders, employees and bank employees as well as customers, to deal with cyber threats that occur well and efficiently so that nothing bad happens. desired next. The process of preventing cyber threats can be described as follows: 1) Thinking about alternative strategies and choosing specific strategies to implement. Bank Syariah Indonesia Pejanggik I Mataram Branch Office has implemented an alternative strategy in measuring company performance to ensure that agreed decisions are achieved and can improve performance after problems occur. 2) Strategy execution mobilizes people in the organization to implement the developed strategy. Bank Syariah Indonesia Pejanggik I Mataram Branch Office has provided education to employees and customers and always incorporates changing patterns of hacker attacks, which can help companies adjust existing strategies. 3) Strategy evaluation. Bank Syariah Indonesia Pejanggik I Mataram Branch Office has reviewed the external and internal factors influencing cyber threats, measured the success of the strategy, and taken corrective action after the cyber threat occurred and the system began to recover.